2021
DOI: 10.1021/acs.jafc.1c00602
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production of Orientin and Vitexin from Luteolin and Apigenin Using Coupled Catalysis of Glycosyltransferase and Sucrose Synthase

Abstract: Orientin and vitexin are flavone 8-C-glycosides that exhibit many biological characteristics. This study aimed to establish a two-enzyme-coupled catalytic strategy to enhance the biosynthesis of orientin and vitexin from apigenin and luteolin, respectively. The C-glucosyltransferase (TcCGT1) gene from Trollius chinensis was cloned and expressed in Escherichia coli BL21­(DE3). The optimal activity of TcCGT1 was achieved at pH 9.0 and 37 °C. TcCGT1 was relatively stable over the pH range of 7.0–10.0 at a tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…It showed that the cascade reaction at 30 °C with pH 8.0 gave the best performance (Figure c,d). Since the supply of UDPG significantly affected the glycosylation reaction, , the concentrations of sucrose and UDP were also optimized. The yield of Reb M reached the maximum when increasing the sucrose concentration from 50 to 600 mM (Figure e).…”
Section: Resultsmentioning
confidence: 99%
“…It showed that the cascade reaction at 30 °C with pH 8.0 gave the best performance (Figure c,d). Since the supply of UDPG significantly affected the glycosylation reaction, , the concentrations of sucrose and UDP were also optimized. The yield of Reb M reached the maximum when increasing the sucrose concentration from 50 to 600 mM (Figure e).…”
Section: Resultsmentioning
confidence: 99%
“…To obtain better control over the glycosylated products formed from 15HCM than was possible by varying the donor/acceptor ratio with UDP-glucose, we turned to a coupled reaction of Bc GT1 and sucrose synthase, with the idea of supplying the UDP-glucose donor in situ from sucrose and UDP. We considered that the sucrose synthase reaction might enable a constant steady-state level of UDP-glucose during the synthesis, contrary to the continuously changing conditions when UDP-glucose is used directly. We were pleased to discover conditions achieving selective production of the disaccharide-modified product at full conversion of the 15HCM substrate, as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The permissive character of the sucrose synthase allows for different nucleotide-activated forms of d -glucose to be prepared from sucrose. ,, Combination with a suitable sugar nucleotide epimerase can expand the scope of glycosyl donors prepared in situ . , Other “reverse” glycosyltransferase reactions previously applied for in situ release of sugar nucleotide donors , can be used in a conceptually analogous manner. Difference should be noted between the idea of in situ sugar nucleotide synthesis for controlling the product selectivity in iterative glycosylation processes, which is new, and use of the same for a mere regeneration of the sugar nucleotide, which is well established for biocatalytic synthesis with glycosyltransferases. …”
Section: Resultsmentioning
confidence: 99%
“…Huang et al used GmSUS from soybean to construct a UDPG regeneration platform, synthesizing a variety of glycosylated small molecules, in which the yield of geranioside was improved up to 99%. 44 More complex natural products like flavone C-glycosides 24 and triterpenoid glycosides 45 have also been efficiently synthesized through this method. For the production of SGs, Chen et al established SUS-UGT cascade reaction systems in E. coli for rebaudioside D 46 and rebaudioside E 47 tuberosum.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The SUSs catalyze a reversible reaction to produce UDPG and fructose from sucrose and UDP (Figure B). Therefore, the SUSs are usually coupled with specific UGTs in whole-cell catalysis to realize cascade reactions of glycosylation and UDPG regeneration. …”
Section: Introductionmentioning
confidence: 99%